Modeling and stability analysis of epidemic expansion disease Ebola virus with implications prevention in population. Issue 1 (1st January 2019) - Tahir, Muhammad; Anwar, Nousheen; Shah, Syed Inayat Ali; Khan, Tahir
Abstract: In this subsection, we presented a mathematical model of Ebola virus (EBOV) proposed by susceptible exposed infected recovered (SEIR) model. In our model, the population is affected by animals. EBOV is an infectious agent causing haemorraghic fever, a severe infectious disease characterised by high fever and bleeding, in humans and some monkeys. Here, we assessed the transmissibility associated with the infection stages of EBOV that generated an epidemic model. In order to do this, in the first step, we formulate the model, and the basic properties of the proposed model are presented. The basic reproductive number is obtained by using the next generation matrix approach. Then, all the endemic equilibrium points related to the disease are derived. We also find the conditions to investigate all possible equilibria of the model in terms of the basic reproduction number (local and global stability). In last, numerical simulation is presented with and without vaccination or control for the proposed model.